Hubungan Fasilitas Belajar Dengan Hasil Belajar Siswa Pada Mata Pelajaran Membuat Busana Wanita Kelas XI Jurusan Tata Busana Di Sekolah Menengah Kejuruan (SMK) Negeri 3 Sungai Penuh - Fitri, Lailatul; adriani, adriani; izwerni, izwerni (Journal of Home Economics and Tourism, 2013)
This research is a quantitative descriptive correlational nature that aims to revealthe relationship of a variable bebes (faslitas learning) with the dependent variable(students' classroom subjects Making On Women's Clothing at SMK Negeri 3Full River). Population in peinelitian numbering 30 people. Samples for the studywere taken from the entire population (sampling saturated), according to all classXI students who have taken courses Creating Clothing Women who were 30students. The data of this study consisted of primary data collected directly fromrespondents with instruments such as questionnaires about student learningfacility on the subjects Creating Women's Clothing, and secondary data obtainedfrom the documentation subject teachers Make Women's Clothing. From theresearch shows that the variable Learning Facility middle category (43.3%) andfor variable Learning Outcomes are mostly located in katerori not pass (60%).Can be seen in the calculation of t count (2.390)> from t table (2.048) so thehypothesis is put forward that is acceptable to the coefficient of determination (r2)= 0.169. Meaningful relationship with the learning outcomes of all studentsstudying in class XI course makes women's clothing 16.9%. So the better thelearning facilities then the higher the student learning outcomes. Kata kunci: Fasilitas belajar, Hasil belajar, mata Pelajaran Membuat BusanaWanita